Comparison between UNS S32101 and UNS S32205 hydrogenated (International Journal of Scientific Research and Management (IJSRM), 2021)
This work presents a study on the duplex stainless steels UNS S32101 and UNS S32205 when subjected to cathodic hydrogenation, to ascertain their behavior under the action of hydrogen. It was evaluated for embrittlement and phase transformations induced by hydrogen, in order to check whether nickel and molybdenum contents would improve resistance to the harmful effects of hydrogen. With the aid of optical (MO) and scanning electron microscopy (SEM), both hydrogen embrittlement in both steels after hydrogenation and degassing was evidenced, as well as pitting corrosion on UNS S32101 duplex stainless steel. It appears that hydrogen can induce the transformation of the austenitic phase (g) into the martensitic phase (α’) in the two duplex stainless steels analyzed and it is verified that hydrogen can lead to the formation of sigma phase at room temperature in duplex stainless steel UNS type S32101